Effect of wind speed and net radiation on the oasis effect in temperate rice paddy fields - Hyunki Kim; Bo‐Kyeong Kim; Hyun‐Dong Moon; Seo‐Ho Shin; Hyeong Ju Lee; Jong‐Sung Ha; Seungtaek Jeong; Jong‐Min Yeom; Yoon Hyung Kim; Jaeil Cho (Agricultural & Environmental Letters)
Abstract The oasis effect, characterized by atmospheric cooling due to excessive evapotranspiration (ET) and the inflow of warm air from the surroundings, has been well documented in vegetated oases. Despite its significant ET rates, the atmospheric cooling phenomenon in rice paddies has not received extensive exploration. This study investigates the oasis effect during July and August, the peak months for ET in rice fields in temperate climate. Over 3 years (2020–2022), energy flux observations using the eddy covariance method were conducted to analyze atmospheric cooling in paddy fields. The findings revealed a pronounced atmospheric cooling effect associated with negative sensible heat in paddy fields. Moreover, this cooling phenomenon exhibited heightened activity during periods of increased wind speeds (>3.5 m/s) and subdued net radiation (<400 W/m2). These results highlight rice paddies' potential to cool the atmosphere, acting as a countermeasure against global warming and the urban heat island effect.